AfricArxiv - the State of Open Access in Africa and its Implication on Researchers (webinar) - Aldirdiri, Osman (My University, 2020)
Presentation slides used to introduce AfricArxiv during the webinar "the State of Open Access in Africa and its Implication on Researchers" organized by TCC Africa.
Keywords: Africa; Open access; Repository